La gimnasia cerebral y la atención en los niños de Primer año de la Escuela de Educación Básica Benjamin Franklin “Science School”, de la ciudad de Riobamba. - Poma Hernández, Evelyn Mishell (2024)
The present research work entitled Brain gymnastics and attention in first-year children of the Benjamín Franklin "Science School" of Basic Education, in the city of Riobamba, was born from the need to determine the importance of brain gymnastics in activation of the attention of children between the ages of 5 - 6 years, specifically the objective of this study is to implement playful strategies necessary for the execution of daily activities in different learning experiences and promote an educational culture based on games and innovative methodologies , with the use of brain gymnastics. The research is developed within a basic and field study, comprising a documentary, descriptive and non-experimental design, supported by a methodology with a qualitative and quantitative approach, with a population of 22 children, The observation technique was applied, the observation sheet was used as an instrument. The data obtained were tabulated, graphed, analyzed and interpreted. It made it possible to demonstrate the lack of attention in children in the first year of basic education. Finally, it is concluded that the application of brain gymnastics is essential to improve attention in the classroom and in any area where children develop, which leads to designing brain gymnastics activities with the purpose of awakening and promoting connections. neurons, which will allow brain activity to be perfected and attention can be better reflected in children at this level.